Remote ischemic perconditioning attenuates acute inflammation of experimental musculocutaneous flaps following ischemia‐reperfusion injury. Issue 2 (9th April 2016) - Krag, Andreas E.; Eschen, Gete T.; Damsgaard, Tine E.; SVÆRDBORG, Mille; Steiniche, Torben; Kiil, Birgitte J.
Abstract : Background: In free flap reconstruction and replantation surgery, prolonged ischemia time may lead to flap or replantation failure. The aim of the study was to investigate the effects of hypothermic flap ischemia or remote ischemic perconditioning (RIPER) during normothermic ischemia on acute inflammation of musculocutaneous flaps subjected to ischemia‐reperfusion injury. Materials and methods : In 24 pigs, a musculocutaneous latissimus dorsi flap was dissected and subjected to 4 hours of arterial ischemia and 7 hours of reperfusion. The animals were allocated into two experimental groups: hypothermic flap ischemia at 4°C ( n  =   8) or normothermic flap ischemia with RIPER ( n  =   8), and one control group with normothermic flap ischemia ( n  =   8). The hypothermic ischemic flaps were cooled in a basin with fresh water and ice. RIPER was initiated 1 hour before reperfusion, by inducing three 10 min cycles of hind limb ischemia with a tourniquet, each separated by 10 min of reperfusion. Acute inflammation was described by inflammatory cytokine secretion (IL‐1β, IL‐6, IL‐10, IL‐12p40, and TNF‐α) from the flap during reperfusion, and by quantitative determination of macrophages in flap biopsies of dermis, subcutaneous tissue, and skeletal muscle following reperfusion. Results : No significant differences were found between normothermic and hypothermic flap ischemia in inflammatory cytokine secretion. However, the IL‐6 secretion was significantly reduced in the RIPER group compared with the control group at 5 hours of reperfusion ( P  =   0.036), and in the RIPER group compared with the hypothermic ischemia group at 3 ( P  =   0 0.0063), 5 ( P  =   0.0026), and 7 hours of reperfusion ( P  =   0.028). The IL‐12p40 secretion was significantly reduced in the RIPER group compared with the control group ( P  =   0.0054) as well as the hypothermic ischemia group ( P  =   0.028) at 5 hours of reperfusion. No significant difference was found among groups in macrophage infiltration. Conclusion : RIPER reduced IL‐6 and IL‐12p40 secretion during reperfusion of porcine musculocutaneous flaps, when compared with hypothermic ischemic flaps and normothermic ischemic flaps without RIPER. © 2016 Wiley Periodicals, Inc. Microsurgery 37:148–155, 2017.